Terbentuknya Cyberstalking Pada Media Sosial Instagram - Akmal Latif, Syahrul; Oktavany, Lindiani (SISI LAIN REALITA, 2021)
Social media is a communication media used by all productive age groups and is the most sensitive place for many aspects of  life,  one of which is the social media instagram there so many technology crimes such as stalking occur and are committed. The purpose of this research is to find out how cyberstalking is formed on social media instagram. Researchers used qualitative method by conducting interview with sources who refferes to the routine activity theory. This phemonenon can lead to perpetrators and victims who can to be happen to anyone and anywhere due to existence of a place, a capable guardians, a suitable target and motivated offender. Cyberstalking can also be an extraordinary crime because it causes many effects of other crimes such as what happens in online comunniaction media today.